Melting-Pot Modernism - Wilson, Sarah, 1973- (Book collections on Project MUSE., 2010)
By tracing the melting-pot impulse toward merging and cross-fertilization through the writings of Henry James, James Weldon Johnson, Willa Cather, and Gertrude Stein, as well as through the autobiography, sociology, and social commentary of their era, Sarah Wilson makes a new connection between the ideological ferment of the Progressive era and the literary experimentation of modernism. Wilson puts literary analysis at the service of intellectual history, showing that literary modes of thought and expression both shaped and were shaped by debates over cultural assimilation. Exploring the depth and nuance of an earlier moment's commitment to cultural inclusiveness, Melting-Pot Modernism gives new meaning to American struggles to imaginatively encompass differenceùand to the central place of literary interpretation in understanding such struggles. --Book Jacket.